The Relationship Between Emotion Regulation and Academic Procrastination in Students of Vocation High School: Hubungan Antara Regulasi Emosi Dengan Prokrastinasi Akademik Pada Siswa SMK - Aditya Nugraha Irawan; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This research motivated by phenomenon students experiencing academic procrastination. This study aims to determine the relationship between emotional regulation and academic procrastination of students at SMK Krian 1 Sidoarjo. This type of research is quantitative using correlational approach. The population was students of class X and XI totaling 1412 students, class XII wasn’t studied because they had graduated. The research sample was 213 students using proportionate stratified random sampling technique. The research data collection technique used the emotional regulation scale (ɑ = 0.800) and the academic procrastination scale (ɑ = 0.917). The data analysis technique uses Pearson's product moment correlation with the help of SPSS 22.0. The results of the analysis research data show the correlation coefficient (r xy) of -0.390 with significance of 0.000 <0.05, meaning that there significant negative relationship between emotional regulation and academic procrastination of students at SMK Krian 1 Sidoarjo. The effect of emotion regulation on academic procrastination in the study was 15.2%